2001
DOI: 10.1126/science.291.5502.319
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Dilated Cardiomyopathy in PD-1 Receptor-Deficient Mice

Abstract: Dilated cardiomyopathy is a severe pathology of the heart with poorly understood etiology. Disruption of the gene encoding the negative immunoregulatory receptor PD-1 in BALB/c mice, but not in BALB/c RAG-2-/- mice, caused dilated cardiomyopathy with severely impaired contraction and sudden death by congestive heart failure. Affected hearts showed diffuse deposition of immunoglobulin G (IgG) on the surface of cardiomyocytes. All of the affected PD-1-/- mice exhibited high-titer circulating IgG autoantibodies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
1,070
3
11

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,644 publications
(1,126 citation statements)
references
References 13 publications
16
1,070
3
11
Order By: Relevance
“…Indeed, B6 mice deficient in Fc␥ receptor IIB (Fc␥RIIB) spontaneously develop circulating antichromatin and anti-dsDNA autoantibodies along with immune complex GN and pulmonary vasculitis, whereas Fc␥RIIB-deficient BALB/c mice do not (56). Moreover, B6 mice deficient in programmed death 1 (PD-1) develop a clinical phenotype highlighted by arthritis and GN (57), whereas BALB/c mice deficient in PD-1 develop no signs of arthritis or GN but do develop a lethal dilated cardiomyopathy (58). Thus, discrete immune disturbances elicit SLE-like features in B6 mice, but the identical immune disturbances do not do so in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, B6 mice deficient in Fc␥ receptor IIB (Fc␥RIIB) spontaneously develop circulating antichromatin and anti-dsDNA autoantibodies along with immune complex GN and pulmonary vasculitis, whereas Fc␥RIIB-deficient BALB/c mice do not (56). Moreover, B6 mice deficient in programmed death 1 (PD-1) develop a clinical phenotype highlighted by arthritis and GN (57), whereas BALB/c mice deficient in PD-1 develop no signs of arthritis or GN but do develop a lethal dilated cardiomyopathy (58). Thus, discrete immune disturbances elicit SLE-like features in B6 mice, but the identical immune disturbances do not do so in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo functions of PD-1, PD-L1, and PD-L2 have been of interest because PD-1 -/-mice progressively develop autoimmune diseases [12,13]. Since previous studies have shown that PD-L2 expression may be regulated in some cell types by Th2 cytokines or Th2 cells [21], and because asthma is believed to be a Th2-driven disease [23][24][25][26][27][28][29][30][31][32], it was of interest to examine whether PD-L2 can play a role in immune regulation in this context.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 has an immunoreceptor tyrosine-based inhibitory motif in its cytoplasmic domain [9][10][11]. Depending on background strain, PD-1 -/-mice develop increased rates of glomerulonephritis, lupus-like arthritis [12], or autoimmune cardiomyopathy [13]. This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In support, PD-1-deficient animals suffer from autoimmune disorders, including lupus-like glomerulonephritis, 10 and dilated cardiomyopathy. 11 The newest member of the B7 family, designated B7-H3, was cloned from a human dendritic cell-derived cDNA library. 12 It is widely expressed in various normal tissues, and its expression can be induced on monocytes and DCs.…”
Section: Introductionmentioning
confidence: 99%